Overview of Parents' Actions in Providing Sexual Education to Preschool-Age Children - Victoria, Silvia Puspa; Neherta, Meri; Fajria, Lili (Indonesian Journal of Global Health Research, 2024)
Children in Indonesia and globally remain vulnerable to sexual violence. Child sexual abuse has a serious impact, both mentally and physically. Objective to determine the description of parents' actions in providing sexual education to preschool-age children. This type of research is a quantitative study with a cross-sectional design. The population in the study were all parents who had preschool-age children. The sample in this study amounted to 270 with simple random sampling technique. The research instrument used a questionnaire consisting of: Parents' education, parents' occupation, parents' knowledge, parents' attitude, exposure to information media, and perception. The dependent variable instrument used the Self-Administered Questionnaire parent's practice of Sex Education. Data were analyzed using SPSS software. The study showed that 29.6% of parents have not provided sexual education, and 70.4% of parents have provided sexual education. Most of the respondents have provided sexual education to their children.